Algorithm of Trauma-Informed Tattooing: Client-Centered Decision - Oliinyk, Kseniia (International Journal of Health Sciences, 2026)
Purpose: To establish a practical, step-by-step algorithm for trauma-informed tattooing that structures shared decision-making, reduces retraumatization risk, and improves patient-reported outcomes (PROs) in both studio and clinical contexts. Methodology: Peer-reviewed literature (2011–2025) on medical and decorative tattooing, psychodermatology, and trauma-informed care was synthesized. The evidence was translated into a procedural workflow with phase-specific checklists and monitoring metrics, including a PRO-focused screening kit and implementation indicators for continuous quality improvement. Findings: The reviewed evidence indicates that medical and reconstructive tattooing can improve satisfaction, body image, and quality of life, with low complication rates when aseptic technique and standard follow-up are used. Trauma-informed implementation is strengthened by a structured, consent-paced approach that expands client choice and control. The resulting algorithm comprises seven phases: pre-screening, environment setup, needs and goals mapping, layered informed consent, co-design with a pain plan, aseptic procedure with micro-pauses, individualized aftercare, and referral pathways. The accompanying PRO kit includes 7- and 30-day satisfaction and distress screening, along with implementation indicators to support ongoing quality improvement. Unique Contribution to Theory, Policy and Practice: This work operationalizes trauma-informed, client-centered tattooing into an actionable workflow that studios and clinical services can adopt immediately. It advances theory by linking trauma-informed principles to observable procedural steps, supports policy by proposing measurable safeguards (checklists, PRO monitoring, referral criteria), and strengthens practice by providing standardized tools that improve consistency, safety, and real-world sustainability while defining priorities for staff training and future research.